Novel Potent Decameric Peptide of Spirulina platensis Reduces Blood Pressure Levels Through a PI3K/AKT/eNOS-Dependent Mechanism. Issue 2 (February 2019) - Carrizzo, Albino; Conte, Giulio Maria; Sommella, Eduardo; Damato, Antonio; Ambrosio, Mariateresa; Sala, Marina; Scala, Maria Carmina; Aquino, Rita Patrizia; De Lucia, Massimiliano; Madonna, Michele; Sansone, Francesca; Ostacolo, Carmine; et al.
Abstract : Considered as a superfood of the future, Spirulina platensis matrix has been extensively used because of its beneficial effect on the management of cardiovascular diseases. However, its nutraceutical properties, bioactive compounds, and molecular mechanisms are unknown. Here, we demonstrate that S platensis matrix processed in vitro by simulated gastrointestinal digestion induces direct endothelial nitric oxide (NO)-mediated vasorelaxation of resistance vessels in mice. To gain insight into the bioactive compounds responsible for this effect, we used a complex multistep peptidomic approach to fractionate the crude digest: of the 5 peptide fractions identified (A–E), only fraction E evoked vasorelaxation. High-resolution mass spectrometry–based screening revealed in E the presence of 4 main peptides (SP3–SP6 [spirulina peptides]), of which only SP6 (GIVAGDVTPI) exerted direct endothelium-dependent vasodilation of ex vivo vessels, an effect occurring via a PI3K (phosphoinositide-3-kinase)/AKT (serine/threonine kinase Akt) pathway converging on NO release. In vivo, administration of SP6 evoked a significant hemodynamic effect, reducing blood pressure, an action absent in eNOS (endothelial NO synthase)-deficient mice. Of note, although lower doses of SP6 had no hemodynamic effects, it still enhanced endothelial NO vasorelaxation. Finally, in an experimental model of arterial hypertension, SP6 exerted an antihypertensive effect, improving endothelial vasorelaxation associated with enhanced serum nitrite levels. Based on our results, this novel decameric peptide may extend the possible fields of application for spirulina-derived peptides and could be developed into a promising nonpharmacological approach for the containment of pathologies associated with vascular NO misregulation. Abstract : Supplemental Digital Content is available in the text.